Investigation of Vaping Fluids Recovered From New York State E-Cigarette or Vaping Product Use-Associated Lung Injury Patients - Lu, Shijun (Jimmy); Li, Lingyun; Duffy, Bryan C.; Dittmar, Mark A.; Durocher, Lorie A.; Panawennage, Deepika; Delaney-Baldwin, Em R.; Spink, David C. (Frontiers in Chemistry, 2021)
E-cigarette or vaping product use-associated lung injury (EVALI) is a serious pulmonary condition that is associated with the extended use of certain vaping products. EVALI was first characterized in the summer of 2019 and has since been reported in all 50 U.S. states. From August 2019 through June 2021, the New York State Department of Health has reported more than 197 confirmed cases emanating from all regions of the state. The Wadsworth Center at the New York State Department of Heath received vaporizer cartridges recovered from EVALI patients for chemical analysis of their contents. Untargeted analytical methods using gas chromatography-mass spectrometry and liquid chromatography-high-resolution mass spectrometry as well as targeted analyses for a variety of analytes including cannabinoids, pesticides, vitamin E acetate (VEA) and mycotoxins were used to characterize the composition of the vaping fluids. From the analyses of the 284 e-cigarette devises recovered from patients, 82 were found to be nicotine-containing pods, and 202 devices containing cannabis oil, apparently from unauthorized or black-market dealers. The fluids from the cannabis-oil cartridges tended to have lower levels of THCs (Δ9-tetrahydrocannabinol + Δ8-tetrahydrocannabinol) and total cannabinoids compared with those of commercially produced formulations and contained significant levels of diluents including VEA, medium-chain triglycerides, polyethylene glycol, and castor oil. VEA was the diluent most frequently detected, which was present in 132 (65.3%) of the vaping fluids that contained cannabis oil. When present, VEA ranged from 1.5 to 68.4% of the total mass of the oil. In some cases, 2 or 3 diluents were detected in the same sample. The ratio of VEA to THCs varied widely, from 0.07 to 5.34. VEA and specifically the high ratios of VEA to THCs in black-market vaping fluids may be causative in EVALI. The safety of additional components and additives that are present in vaping fluids are likewise of concern.